Exciton Delocalization Promotes Far-Red Absorption in a Tetrameric Chlorophyll a Light-Harvesting Complex from Trachydiscus minutus - Seki, Soichiro; Cupellini, Lorenzo; Bína, David; Betti, Elena; Urajová, Petra; Tanaka, Hideaki; Miyata, Tomoko; Namba, Keiichi; Kurisu, Genji; Polívka, Tomáš; Litvín, Radek; Fujii, Ritsuko (ACS Publications, Washington DC, USA, 2025)
Photosynthetic organisms employ light-harvesting complexes (LHCs) to optimize energy capture under variable light conditions. The freshwater eustigmatophyte Trachydiscus minutus accumulates a red-shifted violaxanthin–chlorophyll protein (rVCP) that contributes to far-red light harvesting using only chlorophyll (Chl) a molecules, without chemical modification or substitution of pigments. Based on high-resolution cryo-EM and multiscale quantum chemical calculations, we uncovered a heterodimer-based tetrameric architecture, representing a unique oligomerization mode among LHCs. Within each heterodimer, Chls a are distinctively arranged adjacent to the terminal emitter, forming an unprecedentedly extended chlorophyll cluster. Quantum chemical calculations reveal three strong exciton-coupled pigment domains, two of which reside in the large cluster and solely account for the intense far-red absorption near 700 nm without contributions from charge–transfer states. Our structural and quantum chemical characterizations of far-red light harvesting reveal a molecular mechanism of red spectral tuning that relies on protein-controlled excitonic coupling of identical Chl a pigments, as demonstrated here in this eustigmatophyte, highlighting diverse adaptations for harvesting spectrally shifted, low-energy light.
Keywords: red-shifted violaxanthin–chlorophyll protein, Trachydiscus minutus, red-shifted chlorophyll, photosynthetic light-harvesting system, eustigmatophyte